Intercultural exodus - Pereira, Isabel (2016)
This essay studies the origin and globalization of the Rastafarian movement. Poverty and disenchantment in the inner cities of Kingston gave way in the early 1930's to the black power movement through Marcus Garvey's "Back to Africa" crusade, which eventually led to the appearance of the Rastafarian movement, a "messianic religious and political movement". In this essay, I propose to analyze when, how and why the Rastafarian movement began, its doctrines and the vehicles which were used for its cultural globalization, in other words, the diffusion of the Rastafarian´s beliefs, meanings, ideals and culture outside the borders of Jamaica. My aim is to offer a better understanding of the Rastafarian movement (commonly only associated with the consumption of drugs), so it is important to analyze this study in a cultural point of view. Some authors1 define culture as the way of life that is influenced by behavior, knowledge, and beliefs.The lack of information about a certain culture may lead to the perception that a specific culture is wrong or inferior to ours and this normally causes conflict between individuals. Appreciating and accepting cultural diversity is an ability which helps to communicate effectively in an international way, therefore, leading to the globalization of a certain culture, in this case, of the Rastafarian cultural movement. There is a significant variation within the Rastafarian movement and no formal organization; for example, some Rastafarians see it more as a way of life than a religion, but uniting the diverse movements is the belief in the divinity and/or messiahship of the Ethiopian Emperor Haile Selassie I, the influence of Jamaican culture, the resistance to oppression, and the pride in African heritage.